Characterization of Glycoside Hydrolase Families 13 and 31 Reveals Expansion and Diversification of α-Amylase Genes in the Phlebotomine Lutzomyia longipalpis and Modulation of Sandfly Glycosidase Activities by Leishmania Infection - da Costa-Latgé, Samara Graciane; Bates, Paul; Dillon, Rod; Genta, Fernando Ariel (Frontiers in Physiology, 2021)
Sugar-rich food sources are essential for sandflies to meet their energy demands, achieving more prolonged survival. The digestion of carbohydrates from food is mainly realized by glycoside hydrolases (GH). To identify genes coding for α-glycosidases and α-amylases belonging to Glycoside Hydrolase Family 13 (GH13) and Glycoside Hydrolase Family 31 (GH31) in Lutzomyia longipalpis, we performed an HMMER search against its genome using known sequences from other dipteran species. The sequences retrieved were classified based on BLASTP best hit, analysis of conserved regions by alignment with sequences of proteins with known structure, and phylogenetic analysis comparing with orthologous proteins from other dipteran species. Using RT-PCR analysis, we evaluated the expression of GH13 and GH31 genes, in the gut and rest of the body of females, in four different conditions: nonfed, sugar-fed, blood-fed, and Leishmania mexicana infected females. L. longipalpis has GH13/31 genes that code for enzymes involved in various aspects of sugar metabolism, as carbohydrate digestion, storage, and mobilization of glycogen reserves, proteins involved in transport, control of N-glycosylation quality, as well as others with a putative function in the regulation of myogenesis. These proteins are representatives of GH13 and GH31 families, and their roles seem to be conserved. Most of the enzymes seem to be active with conserved consense sequences, including the expected catalytic residues. α-amylases also demonstrated the presence of calcium and chloride binding sites. L. longipalpis genome shows an expansion in the α-amylase gene family, with two clusters. In contrast, a retraction in the number of α-glucosidases occurred. The expansion of α-amylases is probably related to the specialization of these proteins for different substrates or inhibitors, which might correlate with the higher diversity of plant foods available in the natural habitat of L. longipalpis. The expression of α-glucosidase genes is higher in blood-fed females, suggesting their role in blood digestion. Besides that, in blood-fed females infected with the parasite Leishmania mexicana, these genes were also modulated. Glycoside Hydrolases from families 13 and 31 are essential for the metabolism of L. longipalpis, and GH13 enzymes seem to be involved in the interaction between sandflies and Leishmania.